EPISTEMIC FALLACY MENURUT ROY BHASKAR - Imam Wahyudi; Rangga Kala Mahaswa (Undiksha, 2021)
This article aims to provide an analytical description of Roy Bhaskar's epistemic fallacy and his critique of positivism and postmodernism. The research method uses literature study by referring to epistemology discourse, critical realism view, and the nature of epistemic fallacy. Epistemic fallacy accordingly is the anthropic fallacy because it contains inconsistency in the idea that the argument about being is to be investigated in terms of our knowledge of being. Critical realism finds reductionist and overlapping about what is and what is to be. The epistemic fallacy has also issued several misconceptions, such as uniformitarianism, declining open system, and flat ontology. Therefore, since ontology cannot be reduced into epistemology, relativistic epistemology is part of the Critical Realism notion to overcome solipsism and naïve universalism.